KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DI TINJAU DARI MOTIVASI BELAJAR SISWA PADA MATERI BARISAN DAN DERET - Muhammad Rizal Usman; Andi Alim Syahri; Erni Ekafitria Bahar (Universitas Muhammadiyah Makassar, 2021)
This study aims to determine and describe mathematical problem solving abilities in terms of learning motivation on the material of class XI students at SMK Negeri 4 Gowa. This type of research is a qualitative research using a descriptive approach. Researchers chose 3 students from 30 students who were used as research subjects, these three students represented each of the three categories of learning motivation, namely high, medium, and low learning motivation. The instruments in this study were a learning motivation questionnaire, a problem-solving ability test, and an interview guide. Data collection techniques in the form of questionnaires, tests, and interviews. Data collection techniques in the form of questionnaires, tests, and interviews. The data analysis techniques used are data reduction, data presentation, and conclusion drawing and verification. The results of the research on students' mathematical problem solving abilities based on Polya's steps that appeared at the time of the study: (1) students who had high learning motivation were able to meet the 4 indicators of problem solving ability according to Polya's steps (2) students who had moderate learning motivation were only able to meet 3 indicators of the 4 indicators of problem solving according to Polya's steps (3) students who have low learning motivation are only able to fulfill 2 of the 4 indicators of problem solving abilities according to Polya's steps. It was concluded that students with high and moderate learning motivation had good mathematical problem solving abilities, while students with low learning motivation had poor mathematical problem solving abilities.